Development and Validation of the Adolescent Media Health Literacy Scales: Rasch Measurement Model Approach - Sasha A Fleary (JMIR Publications, 2022)
BackgroundHigh media use has been implicated in negative social and health outcomes among adolescents. Therefore, it is critical that adolescents develop skills to healthily engage with media content. Media health literacy (MHL), skills for assessing and responding to health-related media content, and potentially targetable moderators for the relationship between media use and health-related outcomes are understudied in adolescents. The lack of MHL assessment tools may have contributed to this research gap. ObjectiveThis study aimed to develop and validate test-based scales of adolescents' MHL. MethodsThe items developed were vetted iteratively via community reviews and cognitive interviews to establish content and face validity. Adolescents (N=355) completed a questionnaire that included the revised MHL items. The scales (Recognition/Identification, Influence/Critical Analysis, and Action/Reaction) were validated using Rasch measurement models. Convergent validity was assessed by correlating the summed scores of the three scales with existing functional and internet-related health literacy measures. Criterion validity was assessed by modeling logistic regressions for predicting health literacy-related behaviors from each scale after controlling for demographics. Effect sizes were estimated, and a short form was also validated. ResultsThe final MHL scales (Recognition/Identification, Influence/Critical Analysis, and Action/Reaction) fit their Rasch models. The 9-item Recognition/Identification and 9-item Influence/Critical Analysis scales had good convergent validity with functional and internet-related health literacy measures and were positively related to reading instructions before taking medicines and questioning the truthfulness of health information found online. The 12-item MHL Scales-Short Form also had good convergent and criterion validity. However, convergent and criterion validity were not established for the 3-item Action/Reaction Scale. ConclusionsThe Recognition/Identification and Influence/Critical Analysis scales and the MHL Scales-Short Form may be used to determine the impact of MHL on media use and health outcome relationships and ultimately inform the development of interventions and policies to affect these relationships in multiple settings.